Superconductivity in systems with local attractive interactions - Robaszkiewicz, S.; Micnas, R. (Condensed Matter Physics, 1998)
We discuss approaches based on the concepts of local electron pairing
and the superconducting properties which they imply. The nature of the
intermediate coupling regime is addressed and a recent progress in the
BCS–Bose superconductivity crossover problem is outlined. We also survey
the properties of systems with local attractive interactions consisting
of a mixture of local electron pairs and itinerant fermions coupled via a
charge exchange mechanism which mutually induces superconductivity in
both subsystems. Finally, we briefly discuss the question of a pseudogap
and a possible scenario of crossovers in high temperature superconductors Обговорюються підходи, які базуються на концепціях локального електронного спарювання, і надпровідні властивості, до яких вони приводять. Звертається увага на природу проміжного зв’язку і окреслюються останні досягнення в проблемі кросоверу БКШ - Бозе надпровідність. Зроблено також огляд властивостей систем з локальними притягальними взаємодіями, які складаються з суміші локальних електронних пар і блукаючих ферміонів, що взаємодіють через механізм обміну зарядом, який одночасно індукує надпровідність
в обох підсистемах. Наприкінці коротко обговорюється проблема псевдощілини і можливий сценарій кросоверів у високотемпературних надпровідниках.